Factors influencing consumers green purchase decision in Vietnam - Đỗ, Minh Hạnh (2020)
Derived from the context described above, this present research aimsto contribute prior studies on identifying factors for purchasedecision on green productsof consumers.In particularly, thepresent study examines proposed framework from previoustheoretical studies to understand determinants on consumers’ green purchase based on two theories-social dilemma theory and self-control theory. These determinants are categorized into three groupsincluding individual, situation and social factors. Individual factors are: value (altruism and egoistic), hedonic motivation (novelty seeking), and knowledge.-Situation factors are: perceived behavior control and perceived product efficiency. Social factors are: reference group’s influence (informative, utilitarian and value expressiveinfluences), in-group identityand expectation toothers’ cooperation.This research aim to find answer for research questionwhich is: What factors influence on consumers’ green purchase decision? To what extend these factors impacton consumers’green purchase decision?